Peran Algoritma Pemrograman dalam Pembelajaran Matematika Bagi Mahasiswa Pendidikan Matematika - Dea Putri Ananda Mahela; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research will cover the application of programming algorithms in the context of mathematics learning and transmitting its impact on the quality of mathematics teaching. Therefore, this research aims to understand and explore the potential role of programming algorithms in supporting effective and relevant mathematics teaching. Literary research methods or literary research. Literature research includes reviewing or studying books or reading sources related to algorithm programming in a systematic and organized manner. Writing this article also uses a literature review method or research desk on the results of research that has been carried out previously and is related to the research discussed, especially algorithm programming. To collect some data This is done by looking for reputable journals, reading books. Scientific journals and various sources from website searches, Google Scholar, digital libraries. The results obtained from research articles and several books explain that in learning algorithms, programming has a role related to science or other science subjects such as mathematics and other subjects. These results come from reflections on literature that focuses on understanding and the role of programming algorithms with mathematics. This role includes the ability to make it easier for students with a mathematics background to collect, calculate, or even read data using programs created algorithmically. When we start studying programming algorithms we must first learn the basic concepts of algorithms and programming. In writing algorithms it is never linked to certain rules but only the intent and purpose of each step of the algorithm must be clear and precise. Mathematics learning algorithms are a concept that involves the use of structured and logical steps to teach and understand mathematical concepts to students. The following is a more detailed explanation of the importance of algorithms in mathematics learning: 1. Structured Steps: Algorithms consist of a series of structured and explicit steps to complete a task. math assignment or problem.This is a document that guides students through the process of solving a math problem. 2. Understanding Mathematical Concepts: Algorithms are used to describe and illustrate how to understand certain mathematical concepts. For example, how to calculate the area of ​​a triangle or how to solve linear equations.